2022
DOI: 10.3390/ijerph191912534
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Human Adenovirus in Pakistani Children Hospitalized with Community-Acquired Gastroenteritis under the Age of Five Years

Abstract: Acute gastroenteritis is the major cause of morbidity and mortality among infants and children around the globe. Along with other enteropathogens, human adenovirus (HadV) is a major etiological agent associated with diarrhea in young children. However, information about the epidemiology of Adenoviruses in Pakistan is limited or has not been reported. A total of 1082 stool samples were collected from patients with acute gastroenteritis under the age of five years with symptoms of diarrhea, vomiting, nausea, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Adenoviruses are a group of non-enveloped viruses with doublestranded DNA. Since 1953 when it was first discovered by Rowe et al, more than 120 genotypes have been identified that can infect vertebrates, among which human adenoviruses are classified into seven subgenera from A to G (4)(5)(6). Moreover, different serotypes of adenoviruses are responsible for different types of disease because the tissue affinity of the virus varies (Table 1).…”
Section: Epidemiologymentioning
confidence: 99%
“…Adenoviruses are a group of non-enveloped viruses with doublestranded DNA. Since 1953 when it was first discovered by Rowe et al, more than 120 genotypes have been identified that can infect vertebrates, among which human adenoviruses are classified into seven subgenera from A to G (4)(5)(6). Moreover, different serotypes of adenoviruses are responsible for different types of disease because the tissue affinity of the virus varies (Table 1).…”
Section: Epidemiologymentioning
confidence: 99%